2019
DOI: 10.1001/jamacardio.2019.2589
|View full text |Cite
|
Sign up to set email alerts
|

Association of Biologic Therapy With Coronary Inflammation in Patients With Psoriasis as Assessed by Perivascular Fat Attenuation Index

Abstract: IMPORTANCE Psoriasis is a chronic inflammatory skin disease associated with increased coronary plaque burden and cardiovascular events. Biologic therapy for psoriasis has been found to be favorably associated with luminal coronary plaque, but it is unclear whether these associations are attributable to direct anti-inflammatory effects on the coronary arteries. OBJECTIVE To investigate the association of biologic therapy with coronary inflammation in patients with psoriasis using the perivascular fat attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 16 publications
2
128
2
4
Order By: Relevance
“…Moreover, atherosclerotic plaque size and complex lipid core composition were positively correlated with PVAT volume and macrophage infiltration in a postmortem study of human subjects [13]. Thus, imaging of coronary PVAT holds promise as a non-invasive method to detect unstable coronary lesions [49,50].…”
Section: Clinical Significance Of Pvat Imagingmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, atherosclerotic plaque size and complex lipid core composition were positively correlated with PVAT volume and macrophage infiltration in a postmortem study of human subjects [13]. Thus, imaging of coronary PVAT holds promise as a non-invasive method to detect unstable coronary lesions [49,50].…”
Section: Clinical Significance Of Pvat Imagingmentioning
confidence: 97%
“…Moreover, the PVAT FAI was observed to be beneficial in the risk stratification of patients without coronary artery disease who might benefit from intensive primary therapy to reduce their CVD risk. Elnabawi et al [50] studied the efficacy of novel biologic therapies (i.e. anti-TNF-α, anti-IL-17, and anti-IL12/23 therapy) in psoriasis patients.…”
Section: Clinical Significance Of Pvat Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a systemic inflammatory disease, psoriasis is plagued by comorbidities, including psoriatic arthritis and cardiovascular diseases that may reduce life expectancy . Interestingly, recently Mehta's group showed that treatment with biologics could reduce coronary inflammation and healthcare resource consumption . Furthermore, duration of skin lesions has been linked to the risk of PsA, hypothesizing that early and aggressive intervention may prevent the development of PsA, and perhaps other comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…22 Interestingly, recently Mehta's group showed that treatment with biologics could reduce coronary inflammation and healthcare resource consumption. 23,24 Furthermore, duration of skin lesions has been linked to the risk of PsA, hypothesizing that early and aggressive intervention may prevent the development of PsA, 25 and perhaps other comorbidities. Moreover, we should also pay attention to the Cumulative Life Course Impairment that patients with psoriasis experience, including a heavy burden on their social and mental well-being over several years living with the disease.…”
Section: Introductionmentioning
confidence: 99%